2000
DOI: 10.1042/bj3510557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple proteins expressed in murine embryos as binding partners for the WW domains of the ubiquitin-protein ligase Nedd4

Abstract: Nedd4 is a member of a growing family of ubiquitin-protein ligases which consist of a lipid-binding domain, two to four WW domains and a C-terminal ubiquitin-protein ligase domain. The Nedd4 mRNA levels are developmentally regulated and Nedd4 protein is highly expressed in many mouse embryonic tissues. In this study we have used a far-Western screen to identify embryonic proteins that interact with the WW domains in mouse Nedd4. We report here identification of eight Nedd4 WW-domain-interacting proteins from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 39 publications
3
55
0
1
Order By: Relevance
“…Interestingly, SIMPLE has been identified as the binding partner for the WW domain of the ubiquitin-protein ligase NEDD4 and that interaction was shown to depend on the same PPSY motif (Jolliffe et al, 2000). In addition, we demonstrated that WWOX binding to endogenously expressed SIMPLE was dependent on the amino-terminal WWOX WW domain, consistent with our in vitro ligand-binding experiments.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, SIMPLE has been identified as the binding partner for the WW domain of the ubiquitin-protein ligase NEDD4 and that interaction was shown to depend on the same PPSY motif (Jolliffe et al, 2000). In addition, we demonstrated that WWOX binding to endogenously expressed SIMPLE was dependent on the amino-terminal WWOX WW domain, consistent with our in vitro ligand-binding experiments.…”
Section: Discussionsupporting
confidence: 87%
“…The best characterized targets of Nedd4 and its close homologue Nedd4 -2/ KIAA0439 are the epithelial Na ϩ channel (ENaC) subunits, which interact with Nedd4 WW domains via the PY motifs present in the cytosolic carboxyl termini of each subunit (22-28). As the widespread expression of Nedd4 suggests that it may have additional targets, we carried out a far-Western protein expression screen using the WW domains of Nedd4 as a probe and identified eight new Nedd4 WW domain-binding proteins from mouse embryo cDNA libraries (29). Of these, one encoding a novel protein, which we named N4WBP5, was represented in 25% of clones obtained from the screen (29).…”
mentioning
confidence: 99%
“…This site lies within a consensus 14-3-3 binding site (Figure 1). This motif is identical to one found in the HECT-type E3 ligase Nedd4 (Jolliffe et al, 2000), and Nedd4 function has been shown to be regulated by AKT kinase activity (Boehmer et al, 2003). It is known that phosphorylation of a protein within its 14-3-3 binding site can promote interaction with 14-3-3 (i.e.…”
Section: Rnf11 In Tgf-b Signalingmentioning
confidence: 76%